TIMP-1 resistant matrix metalloproteinase-9 is the predominant serum active isoform associated with MRI activity in patients with multiple sclerosis. (August 2015) - Trentini, Alessandro; Manfrinato, Maria C; Castellazzi, Massimiliano; Tamborino, Carmine; Roversi, Gloria; Volta, Carlo A; Baldi, Eleonora; Tola, Maria R; Granieri, Enrico; Dallocchio, Franco; Bellini, Tiziana; Fainardi, Enrico; et al.
Background: The activity of matrix metalloproteinase-9 (MMP-9) depends on two isoforms, an 82 kDa active MMP-9 modulated by its specific tissue inhibitor (TIMP-1), and a 65 kDa TIMP-1 resistant active MMP-9. The relevance of these two enzymatic isoforms in multiple sclerosis (MS) is still unknown. Objective: To investigate the contribution of the TIMP-1 modulated and resistant active MMP-9 isoforms to MS pathogenesis. Methods: We measured the serum levels of the 82 kDa and TIMP-1 resistant active MMP-9 isoforms by activity assay systems in 86 relapsing–remitting MS (RRMS) patients, categorized according to clinical and magnetic resonance imaging (MRI) evidence of disease activity, and in 70 inflammatory (OIND) and 69 non-inflammatory (NIND) controls. Results: Serum levels of TIMP-1 resistant MMP-9 were more elevated in MS patients than in OIND and NIND ( p < 0.05, p < 0.02, respectively). Conversely, 82 kDa active MMP-9 was higher in NIND than in the OIND and MS patients ( p < 0.01 and p < 0.00001, respectively). MRI-active patients had higher levels of TIMP-1 resistant MMP-9 and 82 kDa active MMP-9, than did those with MRI inactive MS ( p < 0.01 and p < 0.05, respectively). Conclusion: Our findings suggested that the TIMP-1 resistant MMP-9 seem to be the predominantly active isoform contributing to MS disease activity.